2016
DOI: 10.1248/bpb.b15-00756
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Duration of PTH(1–34) Infusion Is One Hour per Day to Increase Bone Mass in Rats

Abstract: Parathyroid hormone (PTH) is a potential medicine for osteoporosis, and subcutaneous (s.c.) PTH treatment enhances bone mass; however, continuous infusion of PTH elicits bone resorption and induces bone loss. To clarify this contradictory phenomenon, we examined bone markers and bone mass in rats to assess the optimal duration of PTH(1-34) infusion. Continuous infusion of PTH at 1 µg/kg/h (C ss , steady-state concentration ca. 300 pg/mL) for 1-4 h clearly stimulated the expression both of bone formation-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…In our study, we found that 18β-GA had little effect on osteoclast precursor proliferation, significantly inhibited RANK expression which subsequently induces differentiation of osteoclast precursors into osteoclasts. After RANKL binding to RANK on preosteoclasts, TRAFs were recruited, which led to the activation of the NF-κB and MAPK pathways ( Shimizu et al, 2016 ; Zeng et al, 2017 ). Treatment with 18β-GA inhibited RANKL-mediated phosphorylation of p65, p50, and IκB in the NF-κB pathway and ERK, JNK and p38 in the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that 18β-GA had little effect on osteoclast precursor proliferation, significantly inhibited RANK expression which subsequently induces differentiation of osteoclast precursors into osteoclasts. After RANKL binding to RANK on preosteoclasts, TRAFs were recruited, which led to the activation of the NF-κB and MAPK pathways ( Shimizu et al, 2016 ; Zeng et al, 2017 ). Treatment with 18β-GA inhibited RANKL-mediated phosphorylation of p65, p50, and IκB in the NF-κB pathway and ERK, JNK and p38 in the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocytes express type-1 PTH/PTHrP receptors (PTH1Rs), which are fully activated by aminoterminal PTH fragments and couple to multiple signal transducers, including adenylyl cyclase and phospholipase C. Intermittent administration of PTH is known to enhance bone mass, while continuous infusion of PTH decreases bone mineral density by increasing bone resorption [26]. Therefore, the regulation of PTH is a very delicate process that depends on the dose and frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous secretion of PTH is associated with increased bone turnover in favor of bone resorption through upregulation of RANKL and downregulation of OPG [ 37 , 38 ]. However, when given intermittently to patients for a short period of time, PTH increases bone turnover in favor of bone formation and is currently used as a treatment for osteoporosis [ 38 , 39 ]. The mechanisms by which PTH regulates RANKL and OPG production in the bone are not completely understood, but the Wnt/ β -catenin pathway is likely to be involved.…”
Section: Overview Of Wnt/ β -Catenin Pathwaymentioning
confidence: 99%